The implications of co-curriculum activities towards students academic performance: the case study in Institut Pengajian Tinggi (IPT) at East Coast - Mohamad Jalin, Nur Hafizah; Wan Din, Wan Zaidiyana; Mohamad Isa, Mohamad Iskandar (2015)
The previous study reveals the fact that involvements in the co-curricular activities do really have an impact on students' academic performance. Most of the studies have been carried out and they have revealed the fact that particular co-curricular activities certainly effects on the academic achievements of the students. The purposed of this study was therefore to investigate the implication of co-curriculum activities towards students' academic performance in Institut Pengajian Tinggi (IPT) at East Coast. The study was conducted by using the questionnaire filling technique which was distributed among 200 students of IPT students at Coast East. The study gave the fact that according to the students involved in any kind of co-curriculum activities their academic performance. Based on the study outcome, all objectives in this research which are to investigate the relationship between students' co-curricular participation and their academic performance, to investigate the factor that affect student academic performance in universities and identify the level of student skills that effect on their academic performance